The influence of students' linguistic condition, school level, and pedagogical input on analytical essay features - Aparici, Melina; Rosado, Elisa; Vilar, Hugo; Cuberos, Rocío; Tolchinsky, Liliana (Frontiers in Language Sciences, 2024)
Analytical essays are a fundamental discourse practice within educational settings. These essays are topic-oriented texts that aim to inform readers about a specific matter while persuading them of the writer's perspective. This study investigates how students' linguistic condition (monolingual vs. bilingual) affects their ability to meet the social and discursive expectations of analytical essays. This is examined both over a broad developmental span, from elementary to higher education, and microdevelopmentally, through a sequence of genre-oriented classroom activities.A corpus of 1,179 essays, written by Spanish monolingual and Catalan/Spanish bilingual students across elementary, secondary, and university levels, was analyzed. Participants were tasked with producing texts on both same and different topics The analysis focused on lexical, syntacticdiscursive and structural features identified as indicators of writing proficiency in the Developing Analytical Writing (DAW) model developed in previous studies. Pedagogical input was controlled by the researchers, and an external evaluation of text quality was performed by teachers from the different school levels.Results indicate that students' linguistic condition influenced most, but not all, the linguistic and structural indicators of writing proficiency but always in interaction with age/school level and pedagogical input. Improvements were observed across school levels and with pedagogical input.Additionally, teachers varied in their appreciation of different facets of writing performance as a function of the participants' age/school level and pedagogical input. However, the linguistic condition of students alone did not significantly impact external evaluations of text quality. Our findings reveal a complex interplay between factors such as writers' linguistic condition, their age/school level, and pedagogical input, which jointly shape the quality of analytical essays.